Directly irradiated fluidized bed autothermal reactor (DIFBAR): Hydrodynamics, thermal behaviour and preliminary reactive tests. (15th August 2023) - Padula, Stefano; Troiano, Maurizio; Tregambi, Claudio; Solimene, Roberto; Salatino, Piero
Highlights: The prototype of a novel solar fluidized bed autothermal reactor is realized. Hydrodynamics of the prototype is characterized by cold flow experiments. Autothermal operation is obtained by a solid–solid countercurrent heat exchanger. Heat transfer coefficients range between 340 and 490 W/(m 2 K). The solar-driven calcination of MgCO3 particles has been achieved. Abstract: The advancements of the Concentrating Solar Thermal (CST) technologies in the heat and power sector are pushing researchers to find new ways to exploit solar energy. Solar-driven thermochemical processes can open new scenarios and set a milestone towards a greener industry. This paper presents the development of a Directly Irradiated Fluidized Bed Autothermal Reactor (DIFBAR), that exploits fluidization technology and the principle of an autothermal reactor to carry out solar chemical processes with high efficiency. The viability of recovering the sensible energy of the solid products to preheat the reactants is studied in an experimental prototype that couples a cavity receiver/reactor and a countercurrent double-pipe heat exchanger. The prototype is operated as a circulating fluidized bed: the inner tube of the heat exchanger is a fluidized bed riser, the receiver works as a gas–solid separator, the outer tube (annulus) of the heat exchanger is an overflow standpipe and a buffer tank (reservoir) connects the annulus to the riser, closing the loop. The reservoir can also be operated as a fluidized bed reactor like in a dual-fluidized bed system. The first experimental results are reported using a Geldart B sand as bed inventory. A hydrodynamic study has been carried out to verify proper control of the system. Solid circulation rates have been determined and match the design target of 1.4 g/s. Pressure measurements have been used to control bed levels and the flow of the sand through the standpipe. The effects of gas velocities and outlet pressure drops are reported. Internal gas flow patterns have been determined by a gas tracing technique. Undesired gas by-passing streams are very small and can be zeroed by regulating the operating conditions. High temperature experiments have been conducted with a high-flux solar simulator under inert and reactive conditions, to prove the operating principle of the reactor. Steady state temperature profiles have been analyzed to assess the performance of the heat exchanger: the heat transfer coefficient ranges between 340 and 490 W/(m 2 K). The operability of a solar-driven chemical process has been proved by calcining a batch of magnesium carbonate (MgCO3 ) particles, added to the inventory.